Organizational climate in a beer company: an exploratory study - Acosta U., Beatriz (2010)
Results presented are part of Cyntia Venegas Gómez Master thesis (2010). Aim was to identify organizational climate in a beer company from Litwin and Stringer’s organizational climate questionnaire, 1968. Participated 49 workers which answered Litwin and Stringer Questionnaire. This has 53 items, divided in 9 scales. Workers perceived a good climate in support, structure, risk, responsibility and warmth and bad climate in conflict, identity, standards and reward. Statistical differences were founded regarding to sex in reward and standards and there weren’t statistical differences in relation to age of the workers.